Creative Construction Conference 2018 - Proceedings 2018
DOI: 10.3311/ccc2018-012
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the roles in the AEC industry to accommodate digital fabrication

Abstract: As robots and other technologies take over tasks previously performed by construction workers and planners, the concern about the future of jobs and wages will increase. While digital fabrication (dfab), and particularly the use of robotic technology, has the potential to improve productivity, it should not necessarily reduce total employment in the construction sector in the long run. It is expected that existing roles will evolve, mainly related to the human-robot interaction, and new roles will be created (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Figure3. Qualitative share of participation of each role vs. degree of digitalization during the execution phase (adapted fromGarcía de Soto et al, 2018b) …”
mentioning
confidence: 99%
“…Figure3. Qualitative share of participation of each role vs. degree of digitalization during the execution phase (adapted fromGarcía de Soto et al, 2018b) …”
mentioning
confidence: 99%
“…These included Dfab engineers, parametric or computational resources, visual-programming conditions, bespoke/customized design and modular features, Dfab optimizing and prefabrication processes, artifact of Dfab physical mockup, value of reducing human dependence, along with risks of increasing uncertainty in production and performance compromise/uncertainty. De Soto et al [111] determined the productivity, cost, and time aspects on the on-site robotic fabrication technology. Results found that complex decoration structures could be made with Dfab at no extra cost.…”
Section: Dfma For Dfabmentioning
confidence: 99%
“…These include Dfab engineers, parametric or computational resources, visual-programming conditions, bespoke/customized design and modular features, digital fabrication optimizing and prefabrication processes, artifact of digital fabrication physical mockup, value of reducing human dependence, along with risks of increasing uncertainty in production and performance compromise/uncertainty. De Soto et al [111] determined the productivity, cost, and time aspects on the on-site robotic fabrication technology. Results found that complex decoration structures can be made with Dfab at no extra cost.…”
Section: Dfma For Dfabmentioning
confidence: 99%